Comparing Characteristics of Early-Onset Injection Drug Users to Those With Late-Onset Injection in Kermanshah, Iran - Jorjoran Shushtari, Z.; Noroozi, A.; Mirzazadeh, A.; Ahounbar, E.; Hajbi, A.; Najafi, M.; Bazrafshan, A.; Farhadi, M.; Farhoudian, A.; Higgs, Peter; Shahboulagh, F.; Waye, K.; et al. (Informa Healthcare, 2017)
© 2017 Taylor & Francis Group, LLC. Background: Characteristics and behaviors of early-onset injection drug users are under studied topics in Iran. This study aimed to identify and compare the demographic characteristics as well as the drug using behaviors of early-onset and late-onset injection drug users in Kermanshah, West Iran. Methods: In this cross-sectional study using snowball and convenience sampling, we recruited 450 people during the Fall of 2014 from two drop in centers in Kermanshah, Iran. We collected data through face-to-face interviews. Early-onset injection is defined as whether the person reported their first injection at 22 years of age or younger. Subsequently, late-onset injection is defined as 23 years of age or older. We compared the characteristics of the two groups through both univariate and multiple logistic analyses. Results: Overall, 54% (CI 95%: 44.3%, 62.2%) were early injectors. After controlling for low socioeconomic status, initiation of drug use at a young age, multiple drug use and methamphetamine use were all significantly associated with a higher likelihood of early-onset injection. Additionally, early-onset injection was associated with recent syringe borrowing (OR = 2.6, p = 0.001), recent syringe lending (OR = 1.4, p = 0.01), recent cooker sharing (OR = 3.2, p = 0.01) and injecting two or more times a day (OR = 2.2, p = 0.04). Conclusion: Early-onset injectors were more likely to report a lower socioeconomic status, initiation of first drug use at a younger age, using methamphetamine alongside polydrug use, and engaging in higher risk taking behaviors like borrowing needles. With these associations, the study emphasizes the need for drug-prevention programs to focus on the transition to injection drug use at younger ages.